Programmatic and Strategic Changes of the Right in Chile (1989-2013) [Cambios Programáticos y Estratégicos de la Derecha en Chile (1989-2013)] - Mella-Polanco, J; Berrios-Guinez, C (Universidad de los Andes, Bogota Colombia, 2019)
Objective/context: The article pursues comprehending the programmatic and strategic trajectory the Chilean right has experienced during the period of 1989-2013. Considering the closeness it had to the Pinochet regime early in the period studied and the electoral competitiveness that has won out in recent five-year periods, is it possible to associate better electoral performance of the sector with changes in programmatic proposals? Methodology: The research uses data from the MARPOR project for Latin America for the purpose of measuring positioning in each election. We also incorporate a historical-narrative analysis of the Chilean right seeking to explore the strategic changes that have been produced vis-a-vis the programmatic change. Conclusions: The results show that the Chilean right have transitioned from deeply conservative programmatic proposals linked to the policies they implemented during the Pinochet dictatorship, to proposals that are closer to the progressive agenda. This has occurred mainly in matters related to social protection (welfare state), education and, in part, in regard to moral issues. The electoral success of the right in recent elections could be associated, at least in part, with this change in the public policy agenda. Originality: In Latin America, the left has usually been studied in great depth: its proposals, organizational structures and, in general, political strategies. The changes on the right have not been analyzed much by political science. This article attempts to contribute in that area focusing on the changes of the right in Chile. This is relevant for the discipline if the current context of the region is considered, where a new wave of right-wing governments has strengthened, and, in particular for the Chilean case, this seeks to contribute to understanding the changes experienced by the Chilean political system over the last thirty years of democracy after the dictatorship. © 2019 Universidad de los Andes, Bogota Colombia. All rights reserved.